2013
DOI: 10.1002/ss.20059
|View full text |Cite
|
Sign up to set email alerts
|

Thriving in College

Abstract: Grades and grads. These two words sum up the typical approach that most institutions of higher education have taken to defi ne student success. Academic performance and graduation rates are easily measured and can be quantified for comparison purposes so that institutions-and entire nations-can gather a snapshot of their own "effectiveness." Yet most faculty and professional staff are keenly aware that this narrow focus misses an important element of the college student experience: whether students are vitally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…To be prepared to navigate both, we suggest that institutions move away from simply using retention as a way to define department success in achieving diversity metrics and instead focus on goals of justice. The focus on justice inspires socially just housing practitioners to shift toward a more robust student thriving framework, which more holistically attends to all aspects of a student's college career (Schreiner, ). Last, community matters.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…To be prepared to navigate both, we suggest that institutions move away from simply using retention as a way to define department success in achieving diversity metrics and instead focus on goals of justice. The focus on justice inspires socially just housing practitioners to shift toward a more robust student thriving framework, which more holistically attends to all aspects of a student's college career (Schreiner, ). Last, community matters.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Although spirituality is the strongest pathway to thriving for African‐American students, sense of community is the second strongest pathway; for all other students, it is the dominant pathway to thriving (Young et al., ). A sense of community has four elements: (a) membership , or a sense of belonging on campus; (b) ownership , or a sense of voice and contribution on campus; (c) relationship , or positive emotional connections to others on campus; and (d) partnership , or working interdependently with others toward mutually desired goals (Schreiner, ). Students who report a strong sense of community on campus feel they are part of a stable and dependable network of people who care about them, are committed to their growth and well‐being, and are able to meet their needs (Lounsbury & DeNeui, ).…”
Section: Pathways To Thrivingmentioning
confidence: 99%
“…In the sophomore year, students’ sense of community on campus contributes significantly to their thriving and success. Schreiner () found that creating and cultivating a sense of community on campus is the “best way to help ALL students thrive” (p. 46, emphasis mine) and specifically is the top predictor of thriving for second‐year students (Schreiner & Young, ). Central to Schreiner's understanding of a sense of community are (a) membership and sense of belonging; (b) ownership and voice; (c) positive relationships; and (d) partnerships with others on campus.…”
Section: Sense Of Community On Campus: the Key To Sophomore Successmentioning
confidence: 99%